2009
DOI: 10.1038/sj.bjc.6605361
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of TRIB3 in colorectal cancer: a novel marker for prognosis

Abstract: BACKGROUND: TRIB3 is a human homologue of Drosophila tribbles. Previous studies have shown that TRIB3 controls the cell growth through ubiquitination-dependent degradation of other proteins, whereas its significance in the prognosis of colorectal cancer (CRC) is not yet fully understood. MATERIALS: This study comprised 202 patients who underwent surgery for CRC, as well as 22 cell lines derived from human gastrointestinal cancer. The correlation of gene expression with clinical parameters in patients was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 43 publications
6
58
1
Order By: Relevance
“…The level of TRB3 mRNA expression was previously demonstrated to be altered in various tumor tissues including liver cancer tissue samples from patients and HCC cell lines (HepG2, Hep3B, Huh-7, HLE and HCF) compared with normal cell lines (12). The present study demonstrated an elevated expression level of TRB3 in MHCC97H cells, ~3.8-fold compared with the expression in the L-02 normal hepatic cell line (Fig.…”
Section: Trb3 Was Overexpressed In Mhcc97h Hcc Cellssupporting
confidence: 65%
See 2 more Smart Citations
“…The level of TRB3 mRNA expression was previously demonstrated to be altered in various tumor tissues including liver cancer tissue samples from patients and HCC cell lines (HepG2, Hep3B, Huh-7, HLE and HCF) compared with normal cell lines (12). The present study demonstrated an elevated expression level of TRB3 in MHCC97H cells, ~3.8-fold compared with the expression in the L-02 normal hepatic cell line (Fig.…”
Section: Trb3 Was Overexpressed In Mhcc97h Hcc Cellssupporting
confidence: 65%
“…A previous study revealed that TRB3 was highly expressed in a number of HCC cell lines under normal conditions or ER stress (12). To the best of our knowledge, the present study identified the first time that the target gene TRB3 is overexpressed in MHCC97H HCC cells in normal conditions.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Some laboratories reported elevated TRIB3 mRNA levels which correlated with bad prognosis in colorectal cancer (46) and breast cancer patients (47). On the other hand, high TRIB3 protein levels have been associated with good prognosis sensitivity to radiotherapy in breast cancer patients (48).…”
Section: Discussionmentioning
confidence: 99%
“…In melanomas, Trib2 facilitates growth and survival by down-regulating FOXO activity (Zanella et al, 2010). Trib levels are increased in lung cancers (Grandinetti et al, 2011), breast cancers (Wennemers et al, 2011a,b), B-cell chronic lymphocytic leukemia (B-CLL Johansson et al, 2010), and cancers of the esophagus and colon (Miyoshi et al, 2009). Because Trib3 is induced in tumors experiencing stress/ starvation conditions, it may contribute to the ability of cells to grow under the nutrient limiting conditions typical within a tumor (Bowers et al, 2003;Schwarzer et al, 2006).…”
Section: Tribs As Oncogenesmentioning
confidence: 99%